Predisposition and Positivism: The Forgotten Foundations of the Entrapment Doctrine - Frampton, T. Ward (2013)
For the past eighty years, the entrapment doctrine has provided a legal defense for defendants facing federal prosecution, but only for those lacking criminal “predisposition” prior to the government’s inducement. The peculiar contours of this doctrine have generated significant academic debate, yet this scholarship has failed to explain why the entrapment doctrine developed as it did in the first instance. This Article addresses this gap by examining competing views on criminality and punishment in America during the doctrine’s emergence, highlighting the significant, though largely forgotten, impact of positivist criminology on the early twentieth-century legal imagination. Though positivism has long since been discredited as a criminological school, positivist theory helped shape the entrapment doctrine, and this intellectual context helps explain several features of the modern defense that have puzzled legal scholars. Unraveling these forgotten theoretical underpinnings thus provides a novel historical perspective on the modern doctrine’s formation and offers a path forward for entrapment law today